Pemecahan Masalah dengan Pendekatan Saintifik dan Koperatif Tipe NHT, serta Peningkatan Kemampuan Komunikasi Matematika Siswa SMP - Valeria Suryani Kurnila; Maria Anita Jau; Sebastianus Fedi; Yohanes Kurniawan (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2018)
This study aims to determine the difference of the mathematical communication skills improvement of students who obtained mathematical learning by problem-solving of scientific approach and Number Head Together (NHT) of cooperative learning and the students who obtained mathematical learning through the use of problem-solving approach only. This research is a quasi-experimental study with nonequivalent control group design. The population of this study was 274 students of 8th-grade who were distributed to seven classes. The samples taken were two classes, each of which consisted of 41 students for the experimental class and 42 students for the control class. The data were analyzed to compare students' mathematical communication skills using descriptive statistics and inferential statistics t-test. The result of this research showed that the mathematical communication skills improvement through the application of problem-solving of scientific approach and NHT of cooperative learning was higher than the mathematical communication skills of students who used a problem-solving approach only.